Using B isotopes and B/Ca in corals from low saturation springs to constrain calcification mechanisms - M. Wall (Nature Portfolio, 2019)
Ocean acidification is expected to have a negative impact on calcifying organisms, however, our understanding of the acclimation potential of corals in their natural habit is currently limited. Here, the authors find that scleractinian corals living in high pCO2 conditions cannot fully adapt the chemistry of their internal calcifying fluid compared to corals growing in ambient conditions.